The paradigm shift in the approach to management of latent tuberculosis infection in high tuberculosis burden countries. (3rd July 2021) - Padmapriyadarsini, Chandrasekaran; Sachdeva, Kuldeep S; Nair, Dina; Ramachandran, Ranjani
ABSTRACT: Introduction : Addressing the reservoir of Latent Tuberculosis Infection (LTBI) is critical to TB elimination because if left untreated LTBI can progress to active TB disease. This additional burden can prevent achieving the global targets of TB elimination. Management of LTBI has been a low priority target for National TB Elimination Programs (NTEP) due to various challenges in the field settings. Areas covered : This article reviews the most recent advances in the field of LTBI management including newer diagnostics, treatments, vaccines, programmatic challenges, and gaps and suggests a way forward that can be adopted by NTEPs for LTBI. We searched the electronic databases of PubMed, Scopus, and Web of Science for studies published between 2010 to 2020 using MeSH terms: Latent TB Diagnosis, TB preventive therapy, Vaccines, LTBI, and HIV/ COVID. Expert opinion : NTEPs of developing countries should offer a better, point-of-care diagnostic, and effective treatment for LTBI to reduce the number of new TB cases arising from people infected with M.tb. Awareness about LTBI should be increased among the health system staff and the public. More funding is needed to advance research as well as implement the newer findings in the NTEP to achieve the End TB targets by 2035.